Apreciación de estudiantes de Medicina latinoamericanos sobre la capacitación universitaria en investigación científica - Mayta-Tristan, Percy (2014)
Background: Learning research skills should be a goal during undergraduate training of physicians. Aim: To identify Latin American medical students’ appraisal on research skills university training. Material and Methods: A self-administered survey about experience in research, self-assessment of research skills, quality of training in the area received at the university and that importance of publishing as undergraduate students, was answered by 208 medical students aged 23 ± 3 years (54% male), attending a medical students congress. Results: Seventy percent of respondents pertained to medical students’ scientific societies and 34% had published in a scientific journal. Fifty two percent considered as good or very good the training level received at their universities on information retrieval and 45% considered good the training in research methodology. Thirty two percent considered as poor or none the training received in scientific writing and 37% in the publishing process. Eighty nine percent considered student publishing as important and 61% perceived limitations in this matter. Conclusions: The university training level received by Latin American medical students on research and publication process was evaluated as deficient by these students